Deciphering the geology of some Darriwilian–Sandbian (Ordovician) ‘ghost’ formations in the UK and North America using olistoliths in marine debris flows - Bergström, Stig M.; FERRETTI, Annalisa (Geological Magazine, 2018)
Olistostromes with calcareous olistoliths are rare components in the Ordovician successions inNWEurope and North America, having been described from only a small number of localities. One of the best exposed, but least known, is in the Garn Formation in coastal outcrops in Anglesey in northwestern Wales. Here, in the graptolite-bearing shales of the Garn Formation, there are numerous limestone olistoliths that are derived from an otherwise unknown ‘ghost’ formation whose original depositional site remains an enigma. These olistoliths contain a Baltoscandian type of conodont fauna that is otherwise unknown in Wales and England. It represents the Baltoniodus variabilis Subzone of the Amorphognathus tvaerensis Zone. Similar, but slightly older, conodont faunas are recorded from olistoliths in the Tweeddale Member of the Shinnel Formation in southern Scotland and in probable olistoliths of the Cobbs Arm Limestone in northeasternmost Newfoundland. Approximately coeval conodont faunas are present in calcareous olistoliths in the Woods Hollow Shale of West Texas and the Womble Shale in the Ouachita Mountains of Arkansas, USA. Lithological and conodont evidence indicates that the calcareous olistoliths were derived from carbonate sediments deposited in relatively shallow water. It is concluded that the study of ‘ghost’ formation olistoliths may provide otherwise unavailable but important data bearing on the marine depositional history of a particular region.